Remarques sur le Psautier Coréite et Asaphite, Ps 42–49 ; 84–85.87–89 - Gosse, Bernard (Biblische Zeitschrift, 2022)
The article outlines the change from the victorious king of Jacob (Ps 44,5) to YHWH Zebaot on Zion (Ps 48,9 ; 84,4 ‘king’), open to all nations (Ps 87). The mediation through David (Ps 89) is in that manner replaced by mediation through Zion (Ps 48 ; 84 ; 87).